Influence of extraction and freeze-drying duration on the effectiveness of Moringa oleifera seeds powder as natural coagulant - Mohamed, Ezzuldin Hasan; Mohammad, Thamer Ahmad; Megat Mohd Noor, Megat Johari; Ghazali, Abdul Halim (Taylor & Francis, 2015)
Moringa oleifera has been proven to be an effective natural coagulant, a suitable alternative to aluminum sulfate, in water treatment. Several studies have been carried out to obtain the efficiency of M. oleifera as a coagulant using different extraction techniques in obtaining the active ingredient, such as, water and salt (different types of salts and varying concentrations). Some studies included adding further processes to convert the extracted M. oleifera into powder form, such as spray-drying and freeze-drying. In this study, the yield and coagulation efficiency of freeze-dried M. oleifera seeds extracted under three different extraction methods (distilled water, potassium chloride and potassium nitrate) at different extraction duration (2 and 15 min); and different freeze-drying durations (24 and 65 h), were investigated. The results showed that the yield of freeze-dried distilled water extracted M. oleifera was neither affected by the duration of extraction or by the duration of freeze-drying. However, the freeze-dried salt extracted M. oleifera showed that the amount recovered through the process increased by 0.85, 60.5, and 40.4% for distilled water, potassium chloride, and potassium nitrate, respectively. When the extraction duration was increased from 2 to 15 min and the freeze-drying duration was increased from 24 to 65 h. In terms of coagulation efficiency, the results showed that for the freeze-dried distilled water extracted M. oleifera, the increase in duration of extraction time and freeze-drying did not improve the coagulation activity. On the contrary, the increase in the extraction and freeze-drying durations increased the optimal dosage from 132 to 163 mg/l and decreased the coagulation efficiency by 2.64%. As for the extraction using potassium chloride or potassium nitrate; the increase of extraction and freeze-drying durations caused a decrease in the optimal dosage from 97 to 70 mg/l for potassium chloride and from 148 to 121 mg/l for potassium nitrate. The coagulation activity of both freeze-dried salt extracted M. oleifera increased by 2.9 and 0.67% for potassium chloride and potassium nitrate respectively. As a conclusion, the salt extraction M. oleifera optimum dosage decreased by 28 and 18% due to the increase of extraction and freeze-drying durations using potassium chloride and potassium nitrate in the extraction process, respectively.